Reproductive behavior and libido of Nordestina breed stallions in an equatorial climate - N.L. Ribeiro; J.C. Oliveira; N.M.V. Silva; S.V. Silva; L.M. Freitas Neto; B.J.P. Farias; F.T.L. Morais; S.G.C.G. Santos; G.R. Medeiros (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objective of this study was to evaluate the reproductive behavior of stallions of the Nordestina breed in an equatorial climate. Eight stallions aged 7 to 19 years, with reproductive experience in natural breeding, were used. Body weight (BW) was measured with the aid of a tape measure and the body condition score (BCS) was evaluated on a scale of 1 to 9. The live weight, body condition and libido of the animals did not show significant differences (P>0.05) between the dry and rainy seasons. The animals were under the same feeding system and presented libido above 4. The average reaction time of the Nordestino stallions was 25.43 seconds, and the older and younger stallions presented different reaction times of 16 and 30 seconds, respectively. The total mounting and ejaculation time was on average 62.05 seconds. Vocalization, Flehmen reflex and smelling are behavioral characteristics most used by stallions at the time of copulation. Nordestino stallions present sexual behavior similar to other equine breeds, however some pre-copulatory responses such as smelling and nibbling, kicking and vocalizing were more evident when compared to other breeds, which may indicate high libido and herd dominance behavior.